4(x-3)+3(x+7)=16

Simple and best practice solution for 4(x-3)+3(x+7)=16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-3)+3(x+7)=16 equation:


Simplifying
4(x + -3) + 3(x + 7) = 16

Reorder the terms:
4(-3 + x) + 3(x + 7) = 16
(-3 * 4 + x * 4) + 3(x + 7) = 16
(-12 + 4x) + 3(x + 7) = 16

Reorder the terms:
-12 + 4x + 3(7 + x) = 16
-12 + 4x + (7 * 3 + x * 3) = 16
-12 + 4x + (21 + 3x) = 16

Reorder the terms:
-12 + 21 + 4x + 3x = 16

Combine like terms: -12 + 21 = 9
9 + 4x + 3x = 16

Combine like terms: 4x + 3x = 7x
9 + 7x = 16

Solving
9 + 7x = 16

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 7x = 16 + -9

Combine like terms: 9 + -9 = 0
0 + 7x = 16 + -9
7x = 16 + -9

Combine like terms: 16 + -9 = 7
7x = 7

Divide each side by '7'.
x = 1

Simplifying
x = 1

See similar equations:

| 61-4=9x+22 | | z-36=58 | | 2n^2+9n-23=3 | | 50x-20=3 | | -3/5x3x3x3 | | 2x-2-4=5 | | 3(1x+1/3)=26 | | 1.5(x+2)=7.5 | | 10(x+4)-3(2x+5)-1=10 | | 112-5x=10x-22 | | b+2a+4c=b | | 1/4x+1/3x+5/6=15/4 | | -8-3=12-8x | | 2r^2-2r-1=0 | | 8+5*lnx-22.6=0 | | 14x-14=0 | | 13-10x=127-32x | | 6-10x=57-31x | | 13-10x=17-32x | | b+2a+4c= | | 3x+4(x-6)+3=0 | | 5/x^3(3x^8) | | x+(17x-18)=90 | | 3p+5=11+2p | | 6m^3+54m^2-6m=0 | | 4n-9=5+3n | | .25q+0.10(2q+6)=7.35 | | p+16p-15=0 | | 5(x-1)-2(x+2)=3 | | 5(4-2c)+3(c+9)=12 | | 4x/5-x/1=x/10-6/2 | | x+(7x-18)=90 |

Equations solver categories